Law on Vietnamese guest workers - The National Assembly (2006)
This Law provides for activities of sending workers abroad under contract; rights and obligations of guest workers under contract; rights and obligations of enterprises and non-business organizations sending workers abroad under contract, and of concerned organizations and individuals.